PERANCANGAN APLIKASI SISTEM INFORMASI AKADEMIK DI SMA ISLAM AL-MIZAN BERBASIS WEB - Yasinta Nurul Aina; Dini Nurfauziyah Rahayu Lestari (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2022)
The needs of educational institutions for IT technology services (Information Technology) vary widely, Al-Mizan Islamic High School is one of the junior high schools in Majalengka district that has a need for IT-based technologyservices. Applications needed to replace the manual process ofmanaging academic information are now computer-based. Thisapplication is expected to help, simplify the management andimplementation of the academic process. Implementation is anapplication designed as a means to develop the potential ofstudents or students to be channeled in web-based academicapplications.